Tissue engineered nigrostriatal pathway for treatment of Parkinson's disease. (3rd June 2018) - Struzyna, Laura A.; Browne, Kevin D.; Brodnik, Zachary D.; Burrell, Justin C.; Harris, James P.; Chen, H. Isaac; Wolf, John A.; Panzer, Kate V.; Lim, James; Duda, John E.; España, Rodrigo A.; Cullen, D. Kacy
Abstract: The classic motor deficits of Parkinson's disease are caused by degeneration of dopaminergic neurons in the substantia nigra pars compacta, resulting in the loss of their long‐distance axonal projections that modulate the striatum. Current treatments only minimize the symptoms of this disconnection as there is no approach capable of replacing the nigrostriatal pathway. We are applying microtissue engineering techniques to create living, implantable constructs that mimic the architecture and function of the nigrostriatal pathway. These constructs consist of dopaminergic neurons with long axonal tracts encased within hydrogel microcolumns. Microcolumns were seeded with dopaminergic neuronal aggregates, while lumen extracellular matrix, growth factors, and end targets were varied to optimize cytoarchitecture. We found a 10‐fold increase in axonal outgrowth from aggregates versus dissociated neurons, resulting in remarkable axonal lengths of over 6 mm by 14 days and 9 mm by 28 days in vitro . Axonal extension was also dependent upon lumen extracellular matrix, but did not depend on growth factor enrichment or neuronal end target presence. Evoked dopamine release was measured via fast scan cyclic voltammetry and synapse formation with striatal neurons was observed in vitro . Constructs were microinjected to span the nigrostriatal pathway in rats, revealing survival of implanted neurons while maintaining their axonal projections within the microcolumn. Lastly, these constructs were generated with dopaminergic neurons differentiated from human embryonic stem cells. This strategy may improve Parkinson's disease treatment by simultaneously replacing lost dopaminergic neurons in the substantia nigra and reconstructing their long‐projecting axonal tracts to the striatum.